Patronising Vaishnava shrines - Mumbai Archive Project Team (Jio Institute, 2024)
Vaishnava communities with Gujarati roots patronise shrines dedicated to manifestations of Lord Vishnu, such as Sri Krishna, Jagannath, and Narayana.